The Arabic Bible from Late Antiquity the Hexateuch from the Syro-Hexapla - Monferrer-Sala, Juan Pedro 1962- (Piscataway, NJ, USA Gorgias Press, 2021)
"The biblical material translated into Arabic during the Middle Ages included texts from the Hexateuch contained in Codex Sinai Arabic 3, the first in the Christian Arabic Texts series now being published. This set of six texts (Pentateuch + Joshua) is of enormous interest, for what it tells us not only about translating into Arabic, and about the techniques and strategies adopted by the translators, but also about the revi-sions and reworkings to which the original translations were subjected, and in general about the transmission process undergone by biblical texts in the hands of successive copyists"--
Includes bibliographical references (Seiten lxi-lxvii)
Text arabisch, Einführung englisch, Titelseite und Impressum in Englisch
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Versions; Bible -- Translating; Bible -- Versions -- Translating